PEMBIMBINGAN DAN EVALUASI KEGIATAN PENGENALAN LAPANGAN PERSEKOLAHAN (PLP) DI SMA 1 REJOTANGAN: MENTORING AND EVALUATION OF INTRODUCTION TO SCHOOL FIELD ACTIVITIES (PLP) AT SENIOR HIGH SCHOOL 1 REJOTANGAN - Noraniza Bahrotul Ilmi; Imelda Ajeng Nur Shinta; Muhammad Wahyu Kusnaeni (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The introduction of school field activities (PLP) is carried out as an effort to form qualified prospective educators. Introduction to school field (PLP) is one of the compulsory courses that must be taken by undergraduate education students. Through PLP, students are expected to improve their pedagogical, social, personality, and professional competencies. PLP is divided into two stages, namely PLP 1 and PLP 2. Activities carried out in PLP 1 include observing school culture and management. Observation of learning activities, making learning tools, and teaching practice are carried out in PLP II. This article discusses the implementation of the school field introduction II (PLP II). The results of the introduction to the field of schooling II are described using a qualitative descriptive method. The evaluation is analysed based on the assessment of the supervising teacher. Based on the evaluation results, students participating in the Bhinneka PGRI University PLP have successfully fulfilled the indicators set in the implementation of PLP activities.